Aumento da incidência de carcinoma basocelular em hospital universitário: 1999 a 2009 - Schmitt, Juliano Vilaverde [UNESP]; Chinem, Valquíria Pessoa; Marques, Mariângela Esther Alencar [UNESP]; Miot, Hélio Amante [UNESP] (Sociedade Brasileira de Dermatologia, 2011)
A incidência do carcinoma basocelular vem aumentando em todos os países. Realizou-se estudo ecológico de 5169 laudos de carcinoma basocelular, da FMB-Unesp, entre janeiro/1999 e dezembro/2009. O incremento médio da incidência para o período foi de 90,6%, projetando-se um diagnóstico para cada 15 pacientes encaminhados à dermatologia. Tal tendência se manteve, mesmo quando indexada pelo número de laudos histopatológicos, movimento hospitalar, atendimentos da dermatologia e população de Botucatu.

The incidence of basal cell carcinoma is increasing worldwide. An ecological study was conducted using the pathology reports from 5169 cases of basal cell carcinoma diagnosed at the Botucatu School of Medicine, Universidade Estadual Paulista Julio de Mesquita Filho (UNESP) between January 1999 and December 2009. The mean increase in the incidence of basal cell carcinoma over this period was 90.6%, suggesting that one case of basal cell carcinoma could be expected for every 15 patients referred to dermatology. This trend was also found when the incidence was indexed according to the absolute number of histopathology exams, the total number of hospital consultations, the total number of dermatological consultations and the population of the town of Botucatu
Increase in the incidence of basal cell carcinoma in a university hospital between 1999 and 2009
Keywords: Carcinoma basocelular; Epidemiologia; Fatores de risco; Incidência; Raios ultravioleta; Carcinoma, basal cell; Epidemiology; Incidence; Risk factors; Ultraviolet rays